Chicken-origin Cluster 3.2 Tembusu virus exhibits higher infectivity than duck-origin Cluster 2 Tembusu virus in chicks - Huang, Yunzhen; Hu, Ziqiang; Dong, Jiawen; Li, Linlin; Zhang, Junqin; Kuang, Ruihuan; Gao, Shimin; Sun, Minhua; Liao, Ming (Frontiers in Veterinary Science, 2023)
In 2020, a chicken-origin Cluster 3 Tembusu virus (TMUV) caused outbreaks of a disease characterized by egg-drop syndrome in laying hens in China. In the present study, a TMUV strain, TMUV-GX, was isolated from tissue samples of laying hens with egg drop syndrome in south China. Phylogenetic analysis grouped TMUV-GX into TMUV Cluster 3.2, which was distinct from the prevalent TMUV Cluster 2 in duck flocks. To study the infectivity and pathogenicity of TMUV-GX in chickens and ducks, 7 day-old specific pathogen-free (SPF) chicks and SPF ducklings were infected with the same dose of the TMUV-GX. As a comparison, the duck-origin Cluster 2 strain, TMUV-JM, infection groups were set up in chicks and ducklings. Compared with the low infectivity and pathogenicity of TMUV-JM in chicks, the chicken-origin TMUV-GX displayed high replication competence in multiple tissues and caused tissues histopathological damage. In addition, the replication competence of TMUV-GX in ducklings was comparable to that of TMUV-JM. Our study revealed chicken-origin Cluster 3.2 TMUV exhibits high infectivity in chicks and ducklings, and suggested that chicken-origin Cluster 3.2 TMUV possesses a biological basis for widespread infection of chickens and ducks.